1999
DOI: 10.2307/2641410
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Habitat and Population Analysis: An Approach to Resolve the Biodiversity Manager's Dilemma

Abstract: Biodiversity managers face a dilemma of choosing between ''coarse-filter'' approaches that deal with the habitats of several species and ''fine-filter'' approaches that address population viability of one or a few species. We present an approach for local spatial scales that integrates habitat-based and population-based methods to focus research and management on the species in a community that are most at risk of extinction and on the places in the landscape most important to these species. The steps in Dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…There may sometimes also be considerable overlap in impacts among these land use types. A study in south western Montana found that density of cowbirds and parasitism of native bird species were significantly associated with density of homes, area in crops, and livestock densities within 6 km of riparian habitats (Hansen et al 1999). Presumably this results because all three of these land use types provide supplemental foods that attract cowbirds.…”
Section: General Effects Of Rrd On Biodiversitymentioning
confidence: 99%
“…There may sometimes also be considerable overlap in impacts among these land use types. A study in south western Montana found that density of cowbirds and parasitism of native bird species were significantly associated with density of homes, area in crops, and livestock densities within 6 km of riparian habitats (Hansen et al 1999). Presumably this results because all three of these land use types provide supplemental foods that attract cowbirds.…”
Section: General Effects Of Rrd On Biodiversitymentioning
confidence: 99%
“…When the population structures of the species at risk are known, the implications of this work can be used to enhance conservation schemes (Van Treuren et al. , 1993; Hansen et al. , 1999; Selinger‐Looten et al.…”
Section: Discussionmentioning
confidence: 99%
“…When the population structures of the species at risk are known, the implications of this work can be used to enhance conservation schemes (Van Treuren et al, 1993;Hansen et al, 1999;Selinger-Looten et al, 1999;Pedroli et al, 2002;Brys et al, 2003). The population dynamics strategies, explaining the regional persistence and patterns in populations, can be useful for guiding the delineation of conservation strategies (Miles, 1979;Lowe, 2002;Freckleton & Watkinson, 2003).…”
Section: A Disorder Approach To River Basinsmentioning
confidence: 99%
“…( 15,16 ) Such models describe predicted species occurrence (presence or absence) on a site based on known species associations with vegetation types and landforms, and other habitat features such as elevation, museum records, and expert opinion. ( 13,16–18 ) An example, for black‐tailed prairie dog, is shown in Fig. 3.…”
Section: Risk‐assessment Methodologymentioning
confidence: 99%